Overexpression of the malate-aspartate NADH shuttle member Aralar1 in the clonal ß-cell line BRIN-BD11 enhances amino-acid-stimulated insulin secretion and cell metabolism - Bender, K.; Maechler, P.; McClenaghan, N.; Flatt, P.; Newsholme, Philip (Portland Press, 2009)
In the present study, we have investigated the effects of the transduction with recombinant adenovirus AdCA-Aralar1 (aspartate-glutamate carrier 1) on the metabolism, function and secretory properties of the glucose- and amino-acid-responsive clonal insulin-secreting cell line BRIN-BD11. Aralar1 overexpression increased long-term (24 h) and acute (20 min) glucose- and amino-acid-stimulated insulin secretion, cellular glucose metabolism, L-alanine and L-glutamine consumption, cellular ATP and glutamate concentrations, and stimulated glutamate release. However, cellular triacylglycerol and glycogen contents were decreased as was lactate production. These findings indicate that increased malate-aspartate shuttle activity positively shifted ß-cell metabolism, thereby increasing glycolysis capacity, stimulus-secretion coupling and, ultimately, enhancing insulin secretion. We conclude that Aralar1 is a key metabolic control site in insulin-secreting cells.